The effects of caffeinated gum and caffeine capsules on running sprint performance - Ispoglou, T.; Barker, H.; Gardiner, D.; Khan, R.; Tester, E. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
Use of anhydrous caffeine is an established and widely used ergogenic method. In sprinting events, optimum performance is highly dependent on the simultaneous peak functioning of a host of physiological systems. Therefore, caffeine supplementation protocols need to be perfectly timed in order to achieve culmination in sprint performance parameters within a narrow time window.